First International M-Libraries Conference 13th – 14th November 2007 - Needham, Gillian (Evidence Based Library and Information Practice, 2007)
The Open University (UK) and Athabasca University (Canada) are hosting the very first international conference to focus on the delivery of library services and resources to users via mobile and handheld devices. This event on November 13th and 14th at the Open University in Milton Keynes will bring together researchers, managers and practitioners from around the world who are interested in extending the value and flexibility of libraries in new and exciting ways. For more details and to register, please visit the website at: http://library.open.ac.uk/mLibraries/.